XXXIII Biennale Internazionale d'Arte Venezia. - Dell'Acqua, Gian Alberto; Marcazzan, Mario; XXXIII Biennale di Venezia, 1966 (Venezia : La Biennale di Venezia, 1966)
Horst Antes ; Ay-O ; Umberto Boccioni ; Ferruccio Bortoluzzi ; Alberto Burri ; Anthony Caro ; Constant ; Piero Dorazio ; Sergio Camargo ; Öyvind Fahlström ; Lucio Fontana ; Yves Gaucher ; Franco Gentilini ; Ezio Gribaudo ; Günter Haese ; Masuo Ikeda ; Robert Jacobsen ; Julio Le Parc ; Etienne Martin ; Fausto Melotti ; Giorgio Morandi ; Bruno Munari ; Arthur Luis Piza ; Rene Portocarrero ; Marina Nunez Del Prado ; Günter Ferdinand Ris ; Emilio Scanavino ; Atanasio Soldati ; Curt Stenvert ; Luigi Veronesi ; Alberto Viani
XXXIII Biennale Internazionale d'Arte Venezia, 18.06 - 16.10.1966
Italiaans
kunstcatalogus